Influenced Factors of Brand Advocacy: The Case of Gen Y Consumers’ Online Travel Agent In Indonesia - Dina Fatimah; Dwina Maretta; Siti Nadhilah; Ricardo Indra; Z. Hidayat (Syntax Corporation, 2022)
Brand advocacy is a fundamental component of a marketing strategy that is created from a genuine relationship with consumers. This research aimed to discover the brand advocacy perceived by Gen Y consumers online travel agents in Indonesia. This study collected 100 samples by purposive sampling technique with the statistical analysis used is Structural Equation Model (SEM). The results of this study prove that customer satisfaction positively affects brand advocacy, customer satisfaction positively affects customer trust, and customer trust positively affects brand advocacy.